2012
DOI: 10.1016/j.jsg.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Deformation bands in porous carbonate grainstones: Field and laboratory observations

Abstract: a b s t r a c tRecent field-based studies documented deformation bands in porous carbonates; these structures accommodate volumetric and/or shear strain by means of pore collapse, grain rotation and/or sliding. Microstructural observations of natural deformation bands in carbonates showed that, at advanced stages of deformation, pressure solution helps to reduce the grain size, enhancing comminuted flow and forming narrow cataclastic zones within the bands. In contrast, laboratory studies on the mechanics of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 59 publications
(146 reference statements)
3
59
1
1
Order By: Relevance
“…12E), but is rare. No band-parallel transgranular pressure solution seams Cilona et al, 2012) are observed.…”
Section: Cataclasis-dominated Compactive Shear Bands (Type 2b)mentioning
confidence: 89%
See 4 more Smart Citations
“…12E), but is rare. No band-parallel transgranular pressure solution seams Cilona et al, 2012) are observed.…”
Section: Cataclasis-dominated Compactive Shear Bands (Type 2b)mentioning
confidence: 89%
“…Natural examples of these bands have been reported since the mid-2000s Micarelli et al, 2006;Tondi et al, 2006). Further studies have followed, including experimental work (Baxevanis et al, 2006;Baud et al, 2009;Vajdova et al, 2010;Zhu et al, 2010;Cilona et al, 2012Cilona et al, , 2014Ji et al, 2015) and field-based studies that document deformation bands predominantly in carbonate grainstones (Antonellini et al, 2008;Agosta et al, 2009;Cilona et al, 2012;Rustichelli et al, 2012;Tondi et al, 2012;Antonellini et al, 2014b), and recently also in chalk (Wennberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations